Mental Health During Crisis: Development and Evaluation of the Post-disaster Spiritual Coping Scale in Turkey - Okan, Nesrullah; Sahin, Yahya (Springer, 2024)
This research presents the detailed development of the post-disaster spiritual coping scale, which aims to evaluate post-disaster spiritual coping processes. The study's first step in developing the scale has been to review the literature on the effects disasters have on the lives of individuals alongside spiritual coping's role in this process. The study has also taken into account the steps required when developing a scale. Data were initially collected from individuals who'd experienced the February 6 Kahramanmaras earthquake, after which the scale items were created. In line with expert opinions, a pilot application of the scale was applied before the items took their final form. During the data collection phase, data were collected three times (N1 = 388, N2 = 194, N3 = 94). Exploratory factor analysis (EFA) was then performed, and the scale was concluded to consist of one dimension and 13 items. Afterward, confirmatory factor analysis (CFA) was performed over the 13-item scale, confirming the results from the previous analysis. The CFA results also showed acceptable goodness-of-fit values to have been obtained (chi 2/df = 2.200; RMSEA = 0.061; SRMR = 0.024; CFI = 0.933; GFI = 0.908). At the same time, each item in the scale was concluded to have a sufficient loading value. As a result of the analysis of internal consistency for the scale, Cronbach's alpha was found to be 0.950. Significant values were also obtained as a result of the criterion validity analysis for the developed scale. In conclusion, the final version of the post-disaster spiritual coping scale has been developed and validated, with the reliability and validity coefficients of the scale being found sufficient. This scale can be used as a powerful tool for evaluating the spiritual coping mechanisms of individuals who are being affected by disaster.
Keywords: Disaster; Spiritual coping; Scale development; Validity; Reliability